Bulbophyllum meihuashanense (Orchidaceae; Epidendroideae) a new species from Fujian, China: evidence based on morphological and molecular data - Li, Can; Fu, Hou-Hua; Lin, Song-Kun; Chen, Xin-Yan; Wu, Jin-Ping; Ma, Liang (Phytotaxa, 2026)
We described and illustrated a new species, Bulbophyllum meihuashanense (Epidendroideae, Orchidaceae), from southern Fujian, China. The new species is morphologically similar to B. yongtaiense, but differs by its shorter blade, flower scape (umbel 2–3 flowered vs. umbel 3–5 flowered), dorsal sepals (with 3-veined vs. 5-veined), petals (gradually acute apex vs. apex obtuse), and lip (ligulate, adaxially shallowly grooved vs. ovate, adaxially deeply grooved). Molecular analysis based on the nuclear (ITS and Xdh) and plastid (matK and psbA-trnH) sequences confirms its status as a new species.